PENGARUH REDUKSI CANAI TERHADAP SIFAT MEKANIS BAJA KARBON RENDAH DENGAN SAMBUNGAN FLASH BUTT WELDING - Sunardi Klaten (Machine : Jurnal Teknik Mesin, 2019)
Steel plate making can be produced by hot and cold rolling method. To obtain the optimal results, the production on the cold rolling mill (CRM) must be carried out continuously. This CRM is equipped with a flash butt welding machine to connect between one plate and anothers. The purpose of this research is to determine the effect of thickness reduction on mechanical properties of steel JIS 3141. The method used in this study is experimental, namely mechanical properties testing at weld area, heat affected zone (HAZ) and base material. The thickness reductions used in this research are 0%, 69,78%, 71,56% and 73,33%. The material characteristics observed were hardness, tensile strength, yield strength, elaongation and corrosion rate. From this study it is known that the thickness reduction 73.33% resulted the best mechanical properties. The values ​​of hardness, tensile strength, yield strength and corrosion rate were 82.26 HRB, 644 N / mm2, 501 N / mm2 and 1.3844 mpy, respectively.